Intraocular Lenses Optic Power Calculation in Extremely Short Eyes - К. B. Pershin; N. F. Pashinova; I. A. Likh; А. Yu. Tsygankov; S. L. Legkikh (Oftalʹmologiâ)
Purpose: to choose the optimal formula for calculating the IOL optical power in patients with an axial eye length of less than 20 mm.Patients and methods. A total of 78 patients (118 eyes) were included in the prospective study. Group I included 30 patients (52 eyes) with extremely short eyes (average axial eye length of 19.60 ± 0.42 (18.54–20.00) mm), group II consisted of 48 patients (66 eyes) with a normal axial length 22.75 ± 0.46 (22.00–23.77) mm with implantation of various monofocal IOL models. The average follow-up period was 13 months. IOL optical power was calculated using the SRK / T formula, retrospective comparison — according to the formulas Hoffer-Q, Holladay II, Olsen, Haigis and Barrett Universal II.Results. In group I, the maximum average estimation error was determined for the formula Haigis (0.88 ± 0.35), then for the formula Olsen, Barrett Universal II, Kane, SRK / T, Holladay 2 and Hoffer-Q (0.51 ± 0.12, 0.16 ± 0.38, 0.13 ± 0.28, 0.10 ± 0.59, 0.05 ± 0.54 and –0.12 ± 0.42, respectively). Similar data were obtained for the average absolute error — for the formulas Haigis, Olsen, Barrett Universal II, SRK / T, Holladay 2, Hoffer-Q and Kane, it was 0.85 ± 0.31, 0.78 ± 0.25, 0.21 ± 0.10, 0.79 ± 0.23, 0.73 ± 0.24, 0.19 ± 0.08 and 0.17 ± 0.06, respectively. When comparing the formulas, significant differences were found for the formulas Hoffer-Q, Barrett Universal II and Kane in comparison with the formulas Haigis, Olsen, SRK / T and Holladay II (p < 0.05) in all cases, respectively, which indicates the advantage of these formulas for the group patients with extremely short eyes. In group II, there were no significant differences between the studied formulas (p > 0.05).Conclusion. This paper presents an analysis of our own data on the effectiveness of six formulas for calculating the IOL optical power in extremely short (less than 20 mm) eyes in comparison with the normal axial length. The advantage of the Hoffer-Q, Barrett Universal II and Kane formulas over Haigis, Holladay 2, Olsen, and SRK / T is shown. To determine the exact indications for using these formulas, further studies are necessary taking into account the anterior chamber depth and a lesser degree of hyperopia.